2010
DOI: 10.1111/j.1756-185x.2010.01548.x
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary fat necrosis, polyarthritis and panniculitis with pancreatic tumor: a case report

Abstract: Acute polyarthritis can occur in non-rheumatic systemic illnesses, presenting a diagnostic dilemma. We present an extremely rare case presenting as acute polyarthritis, panniculitis and medullary fat necrosis with underlying pancreatic pathology. This case report describes a young woman presenting with panniculits, pancreatic tumour, polyarthritis and intra-osseus fat necrosis with a fatal outcome. The medical fraternity needs to be aware of this potentially fatal albeit rare musculoskeletal complication secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
0
14
0
3
Order By: Relevance
“…The underlying pancreatic disease is either acute or chronic pancreatitis [1]. Previous reports have shown that a pancreatic mass, such as a pseudopapillary pancreatic tumor, a malignancy (composed of acinar cell types), or a pancreatic pseudocyst, can also cause PPP syndrome [4][5][6][18][19][20]. Our patient had acute pancreatitis, subcutaneous fat necrosis, and polyarthritis, including medullary fat necrosis.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The underlying pancreatic disease is either acute or chronic pancreatitis [1]. Previous reports have shown that a pancreatic mass, such as a pseudopapillary pancreatic tumor, a malignancy (composed of acinar cell types), or a pancreatic pseudocyst, can also cause PPP syndrome [4][5][6][18][19][20]. Our patient had acute pancreatitis, subcutaneous fat necrosis, and polyarthritis, including medullary fat necrosis.…”
Section: Discussionmentioning
confidence: 79%
“…However, polyarthritis more rarely presents as a complication of pancreatic disease. Therefore, PPP syndrome is extremely rare and presents as a clinical triad of pancreatitis, panniculitis, and polyarthritis [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The underlying pancreatic disease is either acute or chronic pancreatitis [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipase released into the bloodstream in large amounts (and also amylase and trypsin in some cases, although in our patient the amylase level was normal) is responsible for the digestion of subcutaneous fat (panniculitis) and can affect articular surfaces of joints (arthritis) as well as the intramedullary fat of bones [2]. Our patient presented with all three manifestations of the disease.…”
mentioning
confidence: 85%